2020
DOI: 10.3390/en13195009
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the GOx/GCH4 Multi-Element Combustor Including the Effects of Radiation and Algebraic Variable Turbulent Prandtl Approaches

Abstract: Multi-element thrusters operating with gaseous oxygen (GOX) and methane (GCH4) have been numerically studied and the results were compared to test data from the Technical University of Munich (TUM). A 3D Reynolds Averaged Navier–Stokes Equations (RANS) approach using a 60° sector as a simulation domain was used for the studies. The primary goals were to examine the effect of the turbulent Prandtl number approximations including local algebraic approaches and to study the influence of radiative heat transfer (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It is also interesting that the k-epsilon model shows similar values for the Csep = 1 model, and therefore higher values than the GEKO default model. Previously, it was observed that the standard k-epsilon model provides higher pressures than k-omega based models (the shear stress transport model, for example) due to its higher combustion efficiency, originating from the enhanced turbulent mixing [1,2,8,36]. The heat flux values for k-epsilon and GEKO Csep = 1, show the same trend as for the pressure, having higher values for k-epsilon and Csep = 1.…”
Section: Effect Of Detailed Kinetic Mechanismmentioning
confidence: 71%
See 2 more Smart Citations
“…It is also interesting that the k-epsilon model shows similar values for the Csep = 1 model, and therefore higher values than the GEKO default model. Previously, it was observed that the standard k-epsilon model provides higher pressures than k-omega based models (the shear stress transport model, for example) due to its higher combustion efficiency, originating from the enhanced turbulent mixing [1,2,8,36]. The heat flux values for k-epsilon and GEKO Csep = 1, show the same trend as for the pressure, having higher values for k-epsilon and Csep = 1.…”
Section: Effect Of Detailed Kinetic Mechanismmentioning
confidence: 71%
“…It has been shown that RAMEC, in general, results in higher wall heat fluxes, while the Zhukov-Kong mechanism provides better experimental pressure profiles. Due to higher estimated errors in the wall heat flux measurements, and also the absence of modeling of the radiative heat transfer, which can contribute to up to 10-15% of total wall heat flux depending on the wall properties and species concentrations [36,[41][42][43][44], the Zhukov-Kong mechanism, which better agrees with the experimental pressures, can be recommended. Regarding the GEKO coefficients, Csep = 1 can be recommended as well as the standard k-epsilon model for further usage for the same applications, which may be beneficial for engineers in terms of convergence, having turbulence models built on a different basis (k-omega and k-epsilon) and demonstrating similar performances, and, in terms of GEKO, proving to be easily adaptable for the required application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation